Exploring the socio-economic outcomes of Non-Governmental Organizations (NGO) social safety nets in Epworth and Hopley urban suburbs - Zimbabwe - Mutemachani, Cashios (Department of Social Development, 2026)
This study seeks to contribute to scholarship lacking knowledge on the impact of Non- Governmental Organizations' (NGO) social safety net interventions in a context of existing social insecurity in Zimbabwe. The theoretical framework of the Capability Approach and the Ecological Perspective were adopted as the qualitative research and in-depth evaluative tools. A qualitative explorative case study research design was employed to elicit beneficiaries' experiences of NGOs social safety net interventions to gauge the socio-economic effects by examining how poor and vulnerable people survive in a desperate socio-economic environment. The study premised in Zimbabwe upholds the need to consider social safety nets in empowering resource poor urban communities on sustainable livelihoods programs. Using purposive non-probability sampling technique and in-depth face-to-face interviews with a semi-structured open-ended interview schedule, data was collected from a total 21 participants in selected Zimbabwean urban communities. Collected data from the study was thematically analysed which inductively gave rise to the following major findings: social safety nets in the form of cash transfers are an effective policy option in social protection to propel households out of vulnerability and poverty and the study highlighted the great impact of cash transfers in improving household disposable incomes to improve social aspects at family to community level. The study gave an appreciation of improved socio-economic well-being, the urban dwellers in poor urban settlements are susceptible to vulnerability as a result of complex urbanization typified by structural failures. Despite being parsimonious and short-lived as is typical of non-state external actors' social safety net programmes, cash transfers prove to be efficacious in fighting poverty and allowing communities to be resilient and there is great need to invest in these sustainable livelihoods programs that calls for community meaningful and active participation. As another recommendation, cash transfer model in Zimbabwe empowers parents to keep children in school; necessitate investment in economic opportunities and mitigate against mental health risks by restoring human dignity amongst other areas of development at local levels. Thus, both state and non-state actors should resource input towards supporting communities to realise indigenous systems on safety nets programs. Findings from this study illustrate unmitigated gaps in social protection which underscores the need for cooperation between government and external actors. Future research should further explore susceptibility to urban vulnerabilities for social protection planning and interventions.